Analisis Pengaruh Madden-Julian Oscillation (MJO) Terhadap Curah Hujan Ekstrem di Wilayah Kepulauan Kei Sebagai Upaya Mitigasi Bencana Hidrometeorologi - Devika Meilona A Mannu; Jasruddin Jasruddin; Pariabti Palloan (Jurnal Fisika Unand, 2026)
The research has been done with the purpose to examine the impact of MJO propagation on extreme rainfall as a reference for weather forecasting and analysis, especially on extreme rainfall as an efforts to mitigate hydrometeorological disasters in the Kei Islands region. The analysis of MJO activity on extreme rainfall in this study uses the MJO data of phases 4, 5, and 6 with amplitude ≥ 1, and rainfall data in the period of 1997 to 2023, which is processed using the 98th percentile method to obtain extreme rainfall thresholds which are then used to determine trends in the frequency of extreme rain events and the influence of MJO activity. The results show that the trend in the frequency of extreme rain events has a negative value, meaning that extreme rain events will decrease in the future. MJO activity influences ±  30% of extreme rainfall events in the period 1997 to 2023, the other 70% is influenced by other factors. The use of the MJO index as an early warning for mitigation plan on hydrometeorological disaster in Kei Islands could be done by utilizing MJO monitoring and forecasting data accompanied by analysing the atmospheric dynamic conditions